Determining the Bulk Modulus and Microhardness of Tetrahedral Semiconductors - Sanjay Kumar Gorai (Newest Updates in Physical Science Research Vol. 9, 2021)
From electronegativity and principal quantum number of II-VI, III-V semiconductors, a general empirical formula for calculating bulk modulus (B) and microhardness (H) was discovered. Constant C1, which appears in the expression of bulk modulus, as well as constants C2 and C3, which appear in the expression of microhardness and the exponent M, have the following values. The numerical values of C1,C2, C3 and M are respectively 206.6, 8.234, 1.291, -1.10 for II-VI 72.4, 31.87, 7.592, -0.95 for III-V semiconductors. The chemical bonding behaviour of constituent atoms in these semiconductors can be accurately reflected by both electro-negativity and principal quantum number. The measured bulk modulus and microhardness values are very similar to the reported results. The results of this research would aid in the development of new semiconductor materials as well as the investigation of their mechanical properties.